Journalism in the Movies - Matthew C. Ehrlich (University of Illinois Press, 2004)
This is a story of how movies have depicted American journalism from the start of the sound era to the present. It examines such films as The Front Page, His Girl Friday, Mr. Smith Goes to Washington, Citizen Kane, Ace in the Hole, Deadline, USA, All the Presidentâ€™s Men, Network, Absence of Malice, The Killing Fields, Broadcast News, and The Insider. The movies have portrayed journalists both as upstanding citizens and heroes and as scruffy outsiders and villains. Either way, Hollywood has reproduced myths in which the press is always at the heart of things and always makes a difference. The films regularly have suggested that the journalist can see through lies and hypocrisy, stick up for the little guy, uncover the truth, and serve democracyâ€”or that if those things are no longer true because the journalist and the press have lost their way, they were true once upon a time and someday could be true again. Such an argument is both consistent and at odds with the perceptions of many journalists and media critics. They wholeheartedly agree that the press is important. Bill Kovach and Tom Rosenstiel declare that its duty is to provide â€œindependent, reliable, accurate, and comprehensive information that citizens require to be free.â€ That makes journalism every bit as vital as law and medicine, if not more so. In theory, if law is the pursuit of justice and medicine is the pursuit of healing, journalism is the pursuit of truth; seeking and reporting it is the pressâ€™s most important obligation.